Moderasi ESG Risk pada Keputusan Investasi Terhadap Return Saham - Doni Stiadi; Meina Wulansari Yusniar; M. Zainal Abidin (Universitas Lambung Mangkurat, 2023)
financial performance but also relate to the company's sustainability of the environment as a responsibility for the environmental impact of the company's activities. Alignment of corporate responsibilities can be seen in the company's concern for Environmental, Social, and Governance (ESG). This study aims to analyze the role of ESG Risk in moderating the relationship between investment decisions and stock returns in the ESG Leader Index (IDXESGL) group of companies on the Indonesia Stock Exchange (IDX). The sample was selected using the purposive sampling method in 30 companies for the period March 2021-September 2022 with 4 IDXESGL index evaluation periods so that 20 companies were selected and the total observation data was 80 observations. The research data were analyzed using the Moderated Regression Analysis (MRA) method. The results of the analysis show that ESG Risk moderates the effect of investment decisions on stock returns. Therefore, the better the company's ESG performance (the lower the ESG Risk) will strengthen the effect of investment decisions on company performance as indicated by an increase in stock returns, and in the future the company will continue to grow in a sustainable manner. Keywords: ESG Risk, investment decisions, stock returns